ChemInform Abstract: Solid Solution Photocatalyst with Spontaneous Polarization Exhibiting Low Recombination Toward Efficient CO2 Photoreduction. Issue 45 (October 2016) - Zhou, Peng; Wang, Xin; Yan, Shicheng; Zou, Zhigang
Abstract: In view of efficient separation of photogenerated carriers, growth of a polar GaN:ZnO solid solution single crystal along its polarization axis is performed by molten salt ion exchange (space group P63mc, powder XRD).